2020
DOI: 10.1111/cas.14658
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with adult T‐cell leukemia/lymphoma in Japan: A nationwide hospital‐based study

Abstract: Adult T‐cell leukemia/lymphoma (ATL) is a mature T‐cell neoplasm and is classified into four subtypes (acute, lymphoma, chronic, and smoldering) according to the Shimoyama classification, established in 1991 through several nationwide surveys based on the clinical diversity of patients diagnosed in 1983‐1987 in Japan. Thereafter, no such studies have been conducted. Recently, we conducted a nationwide hospital survey using the method of the 1980s studies, collected baseline data on 996 ATL patients diagnosed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 32 publications
2
49
2
Order By: Relevance
“…Regarding this point, a recent study of clinical characteristics of Caribbean ATLL cases found that median age at presentation was 54 years [44]. In a recent national survey in Japan, the median age was 68 years old [45]. Interestingly, the age at ATLL diagnosis is gradually increasing in Japan, and the same trend may be observed in the Caribbean cases in future.…”
Section: Heterogeneity Of Genomic Alterations In Atll: Geographic Regmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding this point, a recent study of clinical characteristics of Caribbean ATLL cases found that median age at presentation was 54 years [44]. In a recent national survey in Japan, the median age was 68 years old [45]. Interestingly, the age at ATLL diagnosis is gradually increasing in Japan, and the same trend may be observed in the Caribbean cases in future.…”
Section: Heterogeneity Of Genomic Alterations In Atll: Geographic Regmentioning
confidence: 95%
“…Interestingly, the age at ATLL diagnosis is gradually increasing in Japan, and the same trend may be observed in the Caribbean cases in future. Prognosis of ATLL also differed between Caribbean and Japanese ATLL cases (median survival time; 5.5 months in the Caribbean acute and lymphoma types, 8.3 months in the Japanese acute type, and 10.0 months in the Japanese lymphoma type) [44,45]. This may be related that number of cases with allogeneic SCT were higher in the Japanese cases than in the Caribbean cases.…”
Section: Heterogeneity Of Genomic Alterations In Atll: Geographic Regmentioning
confidence: 97%
See 1 more Smart Citation
“…As described above, ATLL frequently develops in the elderly, although it has been reported that the age at onset is gradually increasing. 5,29 HTLV-1 is mainly transmitted from mother to child through breastfeeding. [30][31][32] It is, therefore, believed that ATLL develops due to the accumulation of genetic abnormalities over a long period of time after HTLV-1 infection.…”
Section: G Enomi C L Andsc Ape Of Atll In Young Er Individual Smentioning
confidence: 99%
“…57 According to a recent, nationwide, hospital-based study, the acute subtype was the most common, followed by the lymphoma subtype, which was also frequently observed. 29 Among the subtypes, chronic and smoldering are regarded to be indolent ATLL, whereas the lymphoma and acute subtypes are considered to be aggressive ATLL. The chronic subtype is further divided into unfavorable or favorable groups based on laboratory findings.…”
Section: He Terog Eneit Y Of Atll Subt Ype Smentioning
confidence: 99%